Burning bridges, reinventing the American lawn: a strategic approach to residential stormwater management - Sanders, Christopher L. (Kansas State University, 2012)
Wildcat Creek watershed in Riley County, Kansas has been scene to increasingly severe and damaging flooding in recent years. Significant flood events in the summer of 2010 and 2011 have prompted the community to action. One of many areas of concern is addressed by this project in order to facilitate community efforts to reduce future flooding. Residential stormwater best management practices (BMPs) implemented by property owners to reduce the amount of stormwater runoff entering the Wildcat Creek watershed is the focus of this project. An analysis of the residential development typology in the City of Manhattan within the Wildcat Creek watershed guides stormwater BMP implementation strategies. GIS identified residential development types based on land use, land cover, and parcel size. Single family residential and high density multi-family developments are the areas of focus. Rational method stormwater calculations were conducted on one sample site selected from each of four areas identified as unique within the residential context. The four sample sites include large lot single family, small lot single family, traditional single family, and high density multi-family. The current stormwater runoff situation was constructed for residential areas of Manhattan within the Wildcat Creek watershed using these samples. Sample sites were evaluated four times. Existing stormwater runoff amounts for each site were determined. A minimal BMP treatment in the form of rain gardens was applied. Then a moderate BMP treatment including rain gardens, rain barrels, and native plantings was applied. The fourth evaluation was on a high level of rainwater BMP treatment including rain gardens, rain barrels, cisterns, native vegetation, bioretention, and permeable paving. Post-BMP runoff calculations were performed. The resulting data was compared to the pre-BMP stormwater data to determine the impact of varying degrees of BMP treatments. This work produced a series of BMP strategies specifically suited to the Wildcat Creek watershed. These site specific strategies are a valuable resource for community members to help reduce flooding in the watershed. The resulting calculations are also valuable tools for community leaders determining the value of stormwater regulations that may require or promote stormwater BMPs in Manhattan.
Keywords: Wildcat creek; Stormwater; Best management practices; Runoff; Residential; Kansas; Landscape Architecture (0390)